MEDIAN NERVE INJURY IN CHILDREN AGED 2-11 YEARS PRESENTING WITH CLOSED SUPRACONDYLAR FRACTURE OF HUMERUS - Khan, Alam Zeb; Zardad, Shoaib; Adeel, Muhammad; Iqbal, Javed (Journal of Ayub Medical College Abbottabad, 2019)
Background: The supra-condylar humeral fractures are commonest fractures at the elbow in children and represent a third of all limb fractures in children under the age of 7 years. These fractures are associated with neurological deficit and any of the three long nerves of upper arm can be involved in these fractures. This study was conducted to determine the frequency of median nerve injury in children aged 2-11 years presenting with closed supracondylar fracture of humerus. Methods: This descriptive cross-sectional study was conducted at the department of orthopaedics and trauma, Ayub Teaching Hospital Abbottabad from July 2016 to June 2018. One hundred and seventy-one patients with supracondylar fracture of humerus were enrolled. They were treated as per department protocols and the outcome in terms of neurological damage was noted for each study participant. Results: The frequency of neurological damage was 21.05% with median nerve affected most commonly (13.45%). A statistically strong association was found between damage to median nerve and type of fracture, arm involvement and sex of patients (p<0.05) while no statistically significant association with age was obtained. Conclusion: Neurological damage is a common complication of supracondylar humeral fractures with median nerve being the most commonly affected nerve in these fractures. Keywords: Median Nerve; Supracondylar Fracture; Humerus; Open Reduction; Motor Deficit